Theoretical approaches to the use of information and communication technologies in education in the context of the information security of the country - Zelenko, Sergey V. (Journal of the Belarusian State University. Journalism, 2021)
The article presents an extended review of scientific and theoretical sources on the use of information and communication technologies in educational activities of higher educational institutions. The paper investigates negative and positive trends in the use of new technologies in the educational process, defines the criteria for the formation of educational content presented in digital form, and proves the advantage of using electronic teaching aids for the implementation of traditional principles of didactics. Based on the functional characteristics of information and communication technologies, the tasks and principles of education at the present stage are formulated.